CONTINUE TO STRIVE FOR EXCELLENCE AS QS RANKING SOARS, USM VC URGES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 24 March 2016 The Quacquarelli Symonds (QS) World University Rankings by Subject 2016 indicated that Universiti Sains Malaysia (USM) has risen in performance and the USM Chemical Engineering programme is listed among the top 50 in the world (ranked at 46).